Las TIC como herramienta en el proceso de enseñanza-aprendizaje en la escuela de Educación Básica "América y España". - Jácome Pruna, Mayra Beatriz (2021)
This research focused on the lack of Information and Communication Technologies in the teaching- learning process, so nowadays, society demands technological skills in future citizens of the world. This study aimed to determine how ICT is used in the teaching-learning process of the language and literature area of the seventh-year students of Elementary Education of the "América y España" School in the 2020-2021 school year. For this, a methodological design framed in the qualitative- quantitative paradigm was used, combined with the modality of applied research and the type of correlational research, with the participation of 38 teachers and 60 students from the "América y España" School. The main results obtained have corroborated that teachers have a low level of knowledge and mastery of technological tools, so they do not include them regularly in the teaching- learning process, wasting the advantages and possibilities offered by ICT. This proposal consisted of a didactic guide, which has been validated by experts and users, determining its feasibility and viability for solving the problem.